Sarana Navigasi Kognitif Sebagai Upaya Peningkatan Legibilitas Pada Bangunan Mal/Fasilitas-Umum - Magda Bhinnety Etsem; Bimo Walgito; - Sugiyanto; - Priyosulistyo (Jurnal Psikologi, 2007)
Interaction between human and techno-logy sometime is not yet optimum due to the fact that psychological aspect has not been thoroughly considered. Mall is a kind of very attractive public facilities that resemble product of technology. High degree of legibi-lity is needed for optimal use of the mall. The present research is conducted to study: (a) spatial cognition performance of human when short reaction time is demanded, and (b) utilization of such performance with You Are Here (YAH) map as cognitive navigation tool for better legibility. The research method consist of 3 stages: (a) status survey to 20 malls at several big cities in Java, (b) preliminary experiment at a new building with its setting satisfies mall characteristics, and (c) experimental research conducted at a new mall building, involving 160 subjects. Subjects were assigned to do wayfinding tasks, which include: finding a room at the same and different floors. Prior to wayfinding, subjects were asked to look at a YAH map that has been manipulated in terms of the type (North Up Orientation/ NUO or inline egodirection), and its place¬ment rotation (R0, R45, R90, R135, R180, R225, R270, R315). Subjects were assigned to make scats map for assessing their cognitive map representation ability. The following conclusions could be drawn: (a) there is a difference in wayfinding reaction time between YAH map that follow NUO and that of inline; wayfinding reaction time of inline map is lower than that of NUO; (b) there is a difference in wayfinding reaction time among various rotation of YAH map that follow NUO; up to rotation of 1800, the more the rotation the longer the reaction time will be; (c) there is no diffe¬ren¬ce in wayfinding reaction time among various rotation that follow inline principle; (d) there is a difference in the number of direc¬tion mistake during wayfinding bet¬ween YAH map that follow NUO and that of inline; the number of mistake of inline map is lower than that of NUO map; (e) there is a combination of YAH map type and the way it is placed (rotation) that results in relative¬ly shorter wayfinding reaction time, i.e.: those that affecting mental rotation equal to zero; (f) in general all subject possess high cognitive map representation ability that could be utilized in cognitive navigation during wayfinding. Keywords: wayfinding, mental rotation, You Are Here map, cognitive navi-gation